2023
DOI: 10.3389/fimmu.2022.1020844
|View full text |Cite
|
Sign up to set email alerts
|

mRNA vaccines against SARS-CoV-2 induce comparably low long-term IgG Fc galactosylation and sialylation levels but increasing long-term IgG4 responses compared to an adenovirus-based vaccine

Abstract: BackgroundThe new types of mRNA-containing lipid nanoparticle vaccines BNT162b2 and mRNA-1273 and the adenovirus-based vaccine AZD1222 were developed against SARS-CoV-2 and code for its spike (S) protein. Several studies have investigated short-term antibody (Ab) responses after vaccination.ObjectiveHowever, the impact of these new vaccine formats with unclear effects on the long-term Ab response – including isotype, subclass, and their type of Fc glycosylation – is less explored.MethodsHere, we analyzed anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
66
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 95 publications
10
66
1
Order By: Relevance
“…It is important to note that this virus causes severe immune suppression at different levels due to an evolved ability to evade our immune system [13]. There is now compelling evidence that only mRNA vaccines induce a remarkable increase in IgG4 levels, and such an increase was detected in COVID-19 uninfected individuals who received mRNA vaccinations before contracting COVID-19 infection, whereas for patients who had a previous COVID-19 infection before vaccination, IgG4 levels did not rise [94]. This is in contrast with findings from another study showing that the highest IgG4 levels were found in those individuals who developed a breakthrough infection after receiving three doses of mRNA vaccination, indicating that SARS-CoV-2 infections can also induce IgG4 production [11].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is important to note that this virus causes severe immune suppression at different levels due to an evolved ability to evade our immune system [13]. There is now compelling evidence that only mRNA vaccines induce a remarkable increase in IgG4 levels, and such an increase was detected in COVID-19 uninfected individuals who received mRNA vaccinations before contracting COVID-19 infection, whereas for patients who had a previous COVID-19 infection before vaccination, IgG4 levels did not rise [94]. This is in contrast with findings from another study showing that the highest IgG4 levels were found in those individuals who developed a breakthrough infection after receiving three doses of mRNA vaccination, indicating that SARS-CoV-2 infections can also induce IgG4 production [11].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the amount and duration of the spike protein produced are presumably affected by the higher mRNA concentrations in the mRNA-1273 vaccine (100 µg) compared to the BNT162b2 vaccine (30 µg) [94]. Thus, it is probable that the spike protein produced in response to mRNA vaccination is too high and last too much time in the body.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations